PENYEBERANGAN METADATA: ENCODED ARCHIVAL DESCRIPTION, METADATA OBJECT DESCRIPTION SCHEMA, DAN DUBLIN CORE DI PERSIMPANGAN: Array - Gani Nur Pramudyo (Arsip Nasional Republik Indonesia, 2019)
Metadata standards are used for supporting works in resource identification and description, retrieving information, managing information resources, managing intellectual property rights, interoperability and information governance. Implemented metadata are applied by using metadata standard and support interoperability for instance archival and library institutions. Various metadata standards such as Encoded Archival Description, Metadata Object Description Schema and Dublin Core should support this function. This article describes interoperability among the three by using metadata crosswalks. Metadata crosswalks are used to show ability of shared-metadata and exchange to one another. The result of this simple research can be used for material consideration for metadata standards analyzing and metadata interoperability.